The Interactive Effect of Advanced Cancer Patient and Caregiver Prognostic Understanding on Patients’ Completion of Do Not Resuscitate Orders - Shen, Megan Johnson (Psychooncology, 2018)
OBJECTIVE: Advanced cancer patients’ prognostic understanding is associated with completion of Do Not Resuscitate (DNR) orders, which often represent engagement in advance care planning (ACP). Given caregivers’ critical roles in patient decision-making about ACP and end-of-life care, caregivers’ prognostic understanding may have a large additive effect. The present study examined the association between the main and interactive effects of advanced cancer patient and caregiver prognostic understanding on DNR order completion. METHODS: Data were analyzed from a combined dataset of two sequential multi-institutional, longitudinal cohort studies of patients with advanced cancer and their informal caregivers (n=279 dyads) from 2002-2008 [Coping with Cancer 1] and 2010-2015 [Coping with Cancer 2]. Patients’ and caregivers’ prognostic understanding regarding life-expectancy [≤ 12 months (prognostic understanding), > 12 months (lack of prognostic understanding)] was assessed. DNR order completion was assessed through self-report and confirmed through cross-checking with medical records. RESULTS: Multivariable modeling of the main and interactive effects revealed the interactive effect, but not the individual effects, of patients’ and caregivers’ prognostic understanding was significantly associated with higher odds of patients’ DNR order completion, adjusting for potential confounds (AOR=5.89, p=0.04). For dyads in which both the patient and caregiver had prognostic understanding regarding life-expectancy of ≤ 12 months, 70.7% of patients had completed DNR orders compared to 31.6%-38.9% in which one or both lacked prognostic understanding. CONCLUSIONS: Findings highlight the need for ensuring accurate patient and caregiver prognostic understanding in increasing DNR order completion, which may provide a framework for improving engagement in ACP more broadly.